ANALISIS KINERJA MUTU PEKERJAAN STUKTUR BETON BERTULANG PADA PROYEK PEMBANGUNAN HOTEL, MALL, DAN APARTMENT TENTREM KOTA SEMARANG - Putra, Ryan Dwiyana; Nuroji, Nuroji; Suliantoro, Hery (Politeknik Negeri Semarang, 2021)
In Indonesia, infrastructure development is carried out on a large scale. With alarge infrastructure development, it must be balanced with good quality structuralwork performance. On the basis of this, it is necessary to analyze the qualityperformance of reinforced concrete structures in the construction projects of Hotels,Mall and Apartment Tentrem. The research objective was to analyze the qualityperformance from the aspects of strength, density, and dimensions of reinforcedconcrete structures work; analyzing the factors that cause construction defects inreinforced concrete structures work; and find the right strategy in dealing withconstruction defects in reinforced concrete structures work. The research methodused is the method of field inspection, interview and literature method. From thisresearch, the quality performance that does not match the requirements is thedensity aspect. Construction defects in the density aspect are caused bythe formwork that is hollow and there are gaps between the formwork joints, theaddition of water to the fresh concrete mixture, the way to use the vibrator machinedoes not meet the requirements. The strategy for dealing with construction defects isto tighten the supervision of contractors by controlling and evaluating